PENDEKATAN UTAUT UNTUK MENGANALISIS PENGGUNAAN PLATFORM TOKOPEDIA DALAM BELANJA ONLINE (Studi pada Mahasiswa di Kota Malang) - Dhara Ariska Caniago; Yuniarti Hidayah Suyoso Putra (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
The proliferation of e-commerce applications or platforms in Indonesia today provides society, especially students, with increasingly numerous options for online shopping. One example of such an application is Tokopedia. This research analyzes the use of the Tokopedia platform in online shopping utilizing the Unified Theory of Acceptance and Use of Technology (UTAUT) approach. The population in this study is students in the city of Malang, with a sample approach using the Malhotra model, resulting in a sample size of 145 students. The results of SEM-PLS analysis indicate that Performance Expectancy, Effort Expectancy, and Trust have a positive and significant influence on the intention to use Tokopedia for online shopping among students in Malang. Meanwhile, Social Influence and Facilitating Conditions do not have a significant influence on the intention to use Tokopedia for online shopping among students in Malang city. Keywords: UTAUT, E-Commerce Platform, Students, Online Shopping